Implementasi Manajemen Pengetahuan dalam Meningkatkan Motivasi Mengajar di Pondok Pesantren Wali Songo - Miftahatul Rizki, Dina (AL-IBNOR, 2025)
Entrepreneurship training has an important role in developing motivation and innovation in students who are interested in becoming entrepreneurs. However, the lack of skills of some MTsN 36 Jakarta students is an obstacle in taking advantage of these opportunities, thus hampering the potential for entrepreneurial success. Therefore, entrepreneurship training is needed to foster students' interest and skills in entrepreneurship. This research aims to analyze the implementation of entrepreneurship training in increasing students' interest in entrepreneurship carried out by MTsN 36 Jakarta. This research uses a qualitative approach with analytical descriptive methods. The results of the research show that the implementation of entrepreneurship training to increase students' interest in entrepreneurship carried out by MTsN 36 Jakarta has been carried out well. However, in its implementation, inhibiting factors were found in the form of limited resources, such as time and funds. Meanwhile, the supporting factors for the success of implementing entrepreneurship training in increasing students' interest in entrepreneurship found in this research came from the support, commitment and consistency of the school in implementing entrepreneurship training. Keywords: Implementation of Entrepreneurship, Interest in Entrepreneurship, MTsN 36 Jakarta Students